1995
DOI: 10.1074/jbc.270.51.30749
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated Translocation of Cytosolic Phospholipase A2 to the Nuclear Envelope and Endoplasmic Reticulum

Abstract: Cytosolic phospholipase A 2 (cPLA 2 ) is activated by a wide variety of stimuli to release arachidonic acid, the precursor of the potent inflammatory mediators prostaglandin and leukotriene. Specifically, cPLA 2 releases arachidonic acid in response to agents that increase intracellular Ca 2؉. In vitro data have suggested that these agents induce a translocation of cPLA 2 from the cytosol to the cell membrane, where its substrate is localized. Here, we use immunofluorescence to visualize the translocation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
322
6
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(350 citation statements)
references
References 41 publications
21
322
6
1
Order By: Relevance
“…Cytosolic PLA2 is present in almost all cells and mediates the release of arachidonic acid from the lipid bi-layer of the cell membrane (30,31). Inflammatory cytokines IL-1␤ and TNF␣ are stimulants for the activation of the arachidonic acid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic PLA2 is present in almost all cells and mediates the release of arachidonic acid from the lipid bi-layer of the cell membrane (30,31). Inflammatory cytokines IL-1␤ and TNF␣ are stimulants for the activation of the arachidonic acid metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that E6BP associates with and activates endogenous PLA 2 of mammalian origin. Interestingly, immediately after cell activation, cPLA 2 was shown to translocate from the cytosol to the perinuclear envelope and the ER (Schievella et al, 1995), a location where E6BP was found. Moreover, the enzymatic activity of cPLA 2 is calcium dependent (Qiu et al (1998) and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrates that, on activation, cPLA # translocates to the nuclear envelope, where binding to specific regions must occur [11,12]. It is of interest that it has now been shown that annexin V also translocates to this nuclear envelope on cell activation [13] and hence a modulatory role of this annexin on cPLA # cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V has a high intracellular concentration, where it can form up to 2 % of total cell protein in certain tissues [10]. Therefore, considering that both annexin V and cPLA # are found within the cytosol and have both been demonstrated to translocate to the nuclear membrane on increases in intracellular Ca# + levels [11][12][13], it is of importance to investigate mechanisms by which annexin V could modulate cPLA # catalytic activity and, in particular, whether a substrate depletion mechanism could operate successfully in the cell.…”
Section: Introductionmentioning
confidence: 99%